Sistem Pemantauan Cerdas Berbasis Internet of Things pada Pusat Perbelanjaan - Mourio Sutio, Peter; Eka Budiyanta, Nova; Kristina Yanti Hutapea, Duma; Indriati, Kumala (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2022)
Shopping centers in Indonesia are faced with the problem of corona virus pandemic. Shopping centers were temporarily closed by the government and experienced a decline in visitors and even income during the pandemic. In order for shopping centers to earn sufficient income, the government provides a policy for shopping centers by limiting the number of visitors, checking temperature using a thermo scanner or thermo gun, and using masks according to health protocol rules. For this reason, an intelligent monitoring system is needed to monitor the density of the number of visitors and check the temperature automatically to prevent transmission of the corona virus from crowded shopping centers. The intelligent monitoring system is realized in miniature using NodeMCU as a microcontroller, web pages as interface pages for shopping center managers in system monitoring, applications as interface pages for managers in monitoring systems and applications as interface pages for the public so they can see the number of visitors and remaining capacity. at a shopping center. The overall test results percentage obtained is 100% and it can be concluded that the intelligent monitoring system can work well.